Kościół katolicki w Polsce pod rządami komunistów (Politeja, 2016)
Catholic Church in Poland under the rule of communistsAfter the Second World War in Poland was established communist regime. Polish Catholic Church has found in a difficult situation, because official ideology of state became atheistic Marxism‑Leninism. Formal principles of separation between state and Church, freedom of conscience and religion became a facade hiding the atheistic program of regime and its will of rooting out of religion and Church from society. It was already in September 1945 government revoked of the Concordat of 1925. Ruling communists have tried to defeat the Catholic Church one way or another, among them was Trojan Horse method through movement of so‑called “patriotic priests” that have approved the existing regime. On 25 September 1953 was arrested Primate Cardinal Stefan Wyszyński (in seclusion until October 1956). It might be introduction to the general crackdown on Church. After 1956 as a result of destalinisation and political thaw was improved situation of the Catholic Church in Poland. The election of Cracow Cardinal Karol Wojtyła as Pope (assumed name John Paul II) of 16 October 1978 increased the already powerful influence of the Church and his pilgrimages in Poland next years emphasized the historic links between Catholicism and the Polish nation, strengthening a conviction that communism is strange phenomenon in the country.